Monetizing Athlete Brand Image: An Investigation of Athlete Managers’ Perspectives - Olzhas Taniyev; K.C. Mayer; Brian Gordon (Journal of Applied Sports Management, 2022)
In a highly competitive sport marketplace, personal branding is a top priority for athletes. Thusly, marketers should leverage athletes’ talents and influence in creative ways to maximize their earning potential. This research explored the attributes of a marketable athlete, as well as promotional strategies to help secure athlete sponsorships. Semi-structured interviews were conducted with purposefully selected talent marketing practitioners with sport marketing agencies. The findings revealed relatable story, as well as perceived persona, as prevalent themes for a marketable athlete. Additionally, the themes of athlete-brand alignment and social media marketing were important to securing client promotion and sponsorships. These findings extended previous conceptualizations by illuminating the essential role of brand authenticity not only in quality of fan-athlete interaction, but in appeal to prospective sponsors.
Keywords: athlete brand; brand management; brand equity; sport marketing agencies